Personal Self-Actualization in Intensive Group Training, or Why the Adults Need a Non-Professional Education - M. G. Petrova (Образование и наука)
The adults’ modern education, according to the author, can not be limited by obtaining and developing the professional competences, it primarily incorpo- rates the work on life strategies, goals, meanings and self realization activities. The pa- per reveals the research findings concerning the self-actualization peculiarities of the adults choosing different types of socio-psychological trainings for personal growth and self-realization in all spheres of life. The research is aimed at identifying the distinctive features of people who are ready to undergo the trainings and pay for their self-development. The research goals include studying the character profile of people who accept such educational forms as the opportunity for their potential development. It has being found out that striving for educational opportunities in personal grows is the characteristic feature of people real- izing their quality potential as well as the insufficient level of the cognitive recourse.The obtained results prove the necessity of designing the educational programs promoting the adults’ self-awareness and self-development.